Mothers Role Function among Adolescent Menstrual Hygiene in Banten Province - Tri Wahyuni; Ritanti Ritanti (International Journal of Public Health Science (IJPHS), 2022)
Purpose: These study aims were to determine the prevalence of menstrual hygiene and the association between mother’s role function and menstrual hygiene among early adolescent girls in Banten Province, Indonesia.Methodology: This cross-sectional study used simple random sampling technique. The target population including early adolescent girls age 12-15 years old, had menarche. There were 367 respondents in this study that passed the inclusion criteria for the analysis. Multivariable logistic regression was used to determine the association.Results: 46.32 % of respondents noticed the prevalence of good menstrual hygiene. There were 170 out of 367 respondents reported the presence of good menstrual hygiene. The final model of a multiple logistic regression indicated that Mother Support (adj. OR = 6.89, 95% CI: 3.84 – 12.38, p <0.001) and Information Exposure (adj. OR = 2.17, 95% CI: 1.36 – 3.45, p = 0.001) were significantly associated with the bad menstrual hygiene among early adolescent girls in Serang District, Banten Province. Other significant covariate factors were Organization (adj. OR = 1.79, 95% CI: 1.10 – 2.91, p = 0.018).Conclusion: This study found a high prevalence of good menstrual hygiene. Mother support and Information exposure as well as Organization were associated with menstrual hygiene among early adolescent girls in Serang District, Banten Province, Indonesia.